2019
DOI: 10.1177/1090198119885431
|View full text |Cite
|
Sign up to set email alerts
|

Understanding and Influencing Occupational Sedentary Behavior: A Mixed-Methods Approach in a Multiethnic Asian Population

Abstract: We aim to assess sedentary behavior (SB) and its determinants, as well as potential strategies to reduce SB among employees in a tertiary hospital in Singapore, using a mixed-methods approach grounded in the socioecological framework. All employees with email and security guards of a tertiary hospital in Singapore were invited to complete a questionnaire that captured sociodemographics and self-reported domain-specific SB. Environmental influences of occupational SB were assessed using an adapted version of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 48 publications
0
8
0
1
Order By: Relevance
“…Az élmúlt évékbén jéléntősén mégváltózótt az émbérék élétvitélé, mélynék kövétkéztébén az ülő élétmódót fólytató émbérék száma élsősórban a féjlétt órszágókban mégémélkédétt (Rosenkranz et al, 2020). Az ülő élétmódhóz jéléntős mértékbén járul hózzá a munkahélyén üléssél töltött idő, mély némzétközi kutatásók szérint a munkanap hárómnégyédét tészi ki (Ryen et al, 2011; Ryde et al, 2014; Thorp et al, 2012;Wang et al, 2020,). Aggasztó azoknak a kutatásoknak az érédményé, mélyek szerint minél több időt tölt a munkahélyén inaktívan a munkavállaló, annál nagyóbb a valószínűségé, hógy szabadidéjébén is több időt fóg üléssél tölteni (Clemens et al, 2014;Kazi et al, 2014).…”
Section: Bévézété Sunclassified
“…Az élmúlt évékbén jéléntősén mégváltózótt az émbérék élétvitélé, mélynék kövétkéztébén az ülő élétmódót fólytató émbérék száma élsősórban a féjlétt órszágókban mégémélkédétt (Rosenkranz et al, 2020). Az ülő élétmódhóz jéléntős mértékbén járul hózzá a munkahélyén üléssél töltött idő, mély némzétközi kutatásók szérint a munkanap hárómnégyédét tészi ki (Ryen et al, 2011; Ryde et al, 2014; Thorp et al, 2012;Wang et al, 2020,). Aggasztó azoknak a kutatásoknak az érédményé, mélyek szerint minél több időt tölt a munkahélyén inaktívan a munkavállaló, annál nagyóbb a valószínűségé, hógy szabadidéjébén is több időt fóg üléssél tölteni (Clemens et al, 2014;Kazi et al, 2014).…”
Section: Bévézété Sunclassified
“…Due to the significant increase in SB levels in most developed countries over the past century, occupational SB has appeared as a substantial public health issue. The main contributor to the daily sedentary time for workers is the substantial sitting time at the workplace [2]. People may spend three-quarters of the workday in SB [3], and according to Kazi et al, if people spend more time sitting during the workday, they will spend more time sitting during their leisure time [4].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have examined the association between work commitment and sedentary behaviour. Wang et al examined the sedentary behaviour of employees in a tertiary hospital in Singapore and revealed that the median sitting time was five hours/day [ 53 ]. Furthermore, the environment lacked the infrastructure to reduce sedentary behaviour at work [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al examined the sedentary behaviour of employees in a tertiary hospital in Singapore and revealed that the median sitting time was five hours/day [ 53 ]. Furthermore, the environment lacked the infrastructure to reduce sedentary behaviour at work [ 53 ]. Employees also misunderstood that decreasing physical inactivity was equivalent to reducing sedentary behaviour [ 53 ].…”
Section: Discussionmentioning
confidence: 99%